Changes in innovativeness after COVID-19 pandemic - Gonca Telli Yamamoto; Ahmet Selim Karakose (UTMS Journal of Economics, 2020)
COVID-19 pandemic continues to produce substantial effects in various spheres of life in the world. This process is expected to change the attitude and behavior of the society especially by forcing to adopt some technologies, digital means that have not been used before, to keep the social distance and not to enter public areas. The aim of this study is to analyze the changes in innovativeness of people after COVID-19. In this study, to measure the innovativeness of participants, the Innovativeness Scale which was developed by H. Thomas Hurt and others in 1977 was used. The developed questionnaire was distributed via social media and in total data were obtained from 425 participants. The findings of the study revealed that there is a dramatic decrease in the percentage of laggards and there is also a significant increase in innovators, similar changes were seen in other categories as well.
Keywords: O32; M19; L22; 330; COVID-19; diffusion of innovations; innovativeness; S-curve